Impact of Cu incorporation to the cdte thin film properties for photovoltaic application - Rahman K.S.; Aris K.A.; Karim M.R.; Aijaz M.O.; Dar M.A.; Shar M.A.; Misran H.; Amin N. (S.C. Virtual Company of Phisics S.R.L, 2023)
Cadmium Telluride (CdTe) thin films were deposited on cleaned soda lime glass substrates at 300C by RF magnetron sputtering technique. Thin films of Cu were subsequently deposited on top of CdCl2 treated CdTe thin films for 2 min, 5 min, 10 min and 15 min corresponding to a thickness of 20 nm, 50 nm, 90 nm and 120 nm, respectively by sputtering at a substrate temperature of 200C. CdTe and Cu stacks were annealed at 200C for 15 minutes in a vacuum furnace. The influence of different Cu concentration on the structural, topographical, optical, electrical and morphological properties of sputtered CdTe thin films were then investigated by XRD, AFM, UV-Vis, Hall Effect measurement and FESEM, respectively. From the XRD analysis, a sharp CdTe peak corresponding to the (111)cub plane at 2?=23.8 and a low intensity Cu2Te peak representing (200)cub reflection plane at around 2?=24.8 were found for different Cu growth time on CdTe. There was no existence of Cu2Te peak when Cu was deposited on top of CdTe for 2 min. The relative peak intensity was higher for 10 min Cu growth on CdTe. Significant changes were observed in the films surface roughness due to the different Cu concentration. The average and RMS roughness values showed rising trend for higher Cu concentration. The band gap values remained around 1.50 eV for all the films. Electrical measurements showed p-type conductivity and highly degenerate semiconducting behavior with highest carrier concentration of (7.5x1018 cm-3) as achieved for 10 min of Cu growth. Some preliminary CdTe based photovoltaic devices were also fabricated without any process or structural optimization, where the highest photovoltaic conversion efficiency of 3.77% (Voc = 0.42 V, Jsc = 26.4 mA/cm2 and Fill Factor = 0.34) was obtained for the CdTe films having 50 nm thick Cu layer deposited on top. 2018, National Institute R and D of Materials Physics. All rights reserved.